Aplicación de experimentos didácticos motivadores de aprendizaje y desarrollo de habilidades y conocimientos en el área de ciencias naturales en los niños y niñas de séptimo grado de educación básica bloque curricular 5 los ciclos de la naturaleza y sus cambios, de la unidad educativa González Suárez parroquia Chuquiribamba del cantón Loja, período lectivo 2013-2014 - Guaya Satama, Santiago Leonardo (2015)
The research work entitled APPLICATION OF EXPERIMENTS LEARNING TEACHING BOOSTERS AND DEVELOPMENT OF SKILLS AND KNOWLEDGE IN THE AREA OF NATURAL SCIENCES IN CHILDREN OF SEVENTH GRADE OF BASIC EDUCATION CURRICULUM BLOCK 5 CYCLES OF NATURE AND CHANGES's main objective determine the importance of the implementation of the educational experimentation in the school environment, encouraging learning and developing new skills and knowledge in the seventh grade students of Basic Education of the Education Unit Gonzalez Suarez Chuquiribamba parish of Canton Loja 2013-2014 academic year . The research responded to a descriptive design (diagnosis) and quasi-experimental. The methods used in their order were: comprehensive, analytical, synthetic, participatory assessment, models or proactive, workshop, comprehensive evaluation, technical surveys were used as instruments used questionnaires, which were applied to a teacher and 21 students. The main finding: deficiencies with the steps of a school experiment and ignorance of various issues related to the topic of Natural Sciences, can be reduced with the implementation of educational experimentation. As is concluded in this way that applying through the workshop method, experiments with students, their interest in learning through experience and use of different materials to optimize the acquisition of new knowledge in the study of wakes Natural Sciences.